2011
DOI: 10.1007/s12064-011-0134-z
|View full text |Cite
|
Sign up to set email alerts
|

Tunable kinetic proofreading in a model with molecular frustration

Abstract: Abstract. In complex systems, feedback loops can build intricate emergent phenomena, so that a description of the whole system cannot be easily derived from the properties of the individual parts. Here we propose that inter-molecular frustration mechanisms can provide non trivial feedback loops which can develop nontrivial specificity amplification. We show that this mechanism can be seen as a more general form of a kinetic proofreading mechanism, with an interesting new property, namely the ability to tune th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This happened because generalized kinetic proofreading mechanisms were identified [42, 43, 60] making each T cell a context discriminator (or detector). Indeed, in [60] it was shown that in CFSs the dissociation constant that distinguishes alternative pathways before major signals are produced [61] is renormalized by factors related to cell frequencies in the population. The production of major signals was straightforwardly related to long-lived conjugations and it was proposed that the focus for understanding how the adaptive immune system works should be placed on which cells establish those long-lived conjugations.…”
Section: Discussionmentioning
confidence: 99%
“…This happened because generalized kinetic proofreading mechanisms were identified [42, 43, 60] making each T cell a context discriminator (or detector). Indeed, in [60] it was shown that in CFSs the dissociation constant that distinguishes alternative pathways before major signals are produced [61] is renormalized by factors related to cell frequencies in the population. The production of major signals was straightforwardly related to long-lived conjugations and it was proposed that the focus for understanding how the adaptive immune system works should be placed on which cells establish those long-lived conjugations.…”
Section: Discussionmentioning
confidence: 99%
“…One of these, based on "energy relay" will be discussed later in this section. Another kinetic proofreading scheme [259] is based on "inter-molecular frustration".…”
Section: Specificity Amplification By Energy Dissipation: Kinetic Pro...mentioning
confidence: 99%
“…Important consequences can result if major events in a population only take place when agents are matched for a minimum amount of time. This happens for certain reactions in biomolecular systems [38, 39], the cellular activation in immunology [1, 40, 41] or reproduction in evolutionary biology populations [42]). Then, it becomes clear that, despite the fact that all agents continuously interact, some will never react.…”
Section: Brief Introduction To the Cellular Frustration Frameworkmentioning
confidence: 99%